Penyuluhan Senam Otak untuk Meningkatkan Kemampuan Kognitif pada Komunitas Lansia di Wilayah Puskesmas Mojolaban Kota Surakarta - Ilvia Rema Viani; Arin Supriyadi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Mojolaban is one of the sub-districts in Sukoharjo Regency, Central Java. Mojolaban Sub-district has a Health Center as its role in the field of public health at the first level with 2 health centers, namely Mojolaban Health Center as the main health center and Jati Malang Health Center as a supporting health center. The 10 largest number of diseases in Mojolaban Health Center is in the elderly. When the elderly experience a degenerative process due to the aging process, one of which is changes in the neurological system so that the elderly experience cognitive decline. The purpose of this program is to help provide education, prevention and maintain these changes so that they do not worsen. The method used is education in the form of counseling and providing leaflets to the Healthy Jaya Abadi Elderly Post Community in Wirun Village. The results of the pre-test and post-test questionnaires to assess understanding showed a significant increase in understanding with an average pre-test value of 20% and an average post-test value of 80%.